HUBUNGAN TINGKAT PENDIDIKAN DAN AKTIFITAS FISIK TERHADAP FUNGSI KOGNITIF LANSIA USIA 60 TAHUN DI WILAYAH KERJA PUSKESMAS GOMBONG II KABUPATEN KEBUMEN - Nugroho, Irmawan Andri; Asti, Arnika Dwi; Kuatno, Lia (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
The brain is a part of the human body that functions as a cognitive center. When the brain begins to age there will be a decline in brain function which can lead to a decline in cognitive function and balance of the body, so that an elderly person will experience memory loss. After the elderly retire or stop working, the physical activity routine will decrease. This will have an impact on the level of concentration and cognitive status in the elderly. Groups with low education are not perceived to be better cognitively compared to groups with higher education. The study was conducted in the Gombong II Community Health Center Work Area of Kebumen District in May-June 2017 by distributing questionnaires on physical activity assessment, education and cognitive level measurement using the MMSE questionnaire. Sampling was conducted in cross sectional with 35 respondents. The results of the Chi-Square test obtained a significance value of p <0.001 which means that there is a significant relationship between the level of education and cognitive of the elderly. Test the level of activity relationship obtained p value 0.045, which means that there is a significant relationship between the level of physical and cognitive activity of the elderly in the Gombong II Community Health Center Work Area. There is a significant relationship between the level of education and physical activity on cognitive elderly aged 60 years in the Gombong II Community Health Center Work Area. To the community, especially those who are elderly, they should increase their activities in order to maintain cognitive function in the elderly so that the quality of life of the elderly can be increased..Key word : Cognitive, activity, education